The essentials of statistics a tool for social research - Healey, Joseph F. (Wadsworth Cengage Learning, 2013)
Healey's practical, easy-to-follow book explains the basics of statistics, emphasizing practical application and skill development rather than complicated math. The text's numerous study tools help you review concepts and prepare for examinations